Variants in ACTG2 underlie a substantial number of Australasian patients with primary chronic intestinal pseudo‐obstruction. Issue 9 (21st May 2018) - Ravenscroft, G.; Pannell, S.; O'Grady, G.; Ong, R.; Ee, H. C.; Faiz, F.; Marns, L.; Goel, H.; Kumarasinghe, P.; Sollis, E.; Sivadorai, P.; Wilson, M.; et al.
Abstract: Background: Primary chronic intestinal pseudo‐obstruction (CIPO) is a rare, potentially life‐threatening disorder characterized by severely impaired gastrointestinal motility. The objective of this study was to examine the contribution of ACTG2, LMOD1, MYH11, and MYLK mutations in an Australasian cohort of patients with a diagnosis of primary CIPO associated with visceral myopathy. Methods: Pediatric and adult patients with primary CIPO and suspected visceral myopathy were recruited from across Australia and New Zealand. Sanger sequencing of the genes encoding enteric gamma‐actin ( ACTG2 ) and smooth muscle leiomodin (LMOD1) was performed on DNA from patients, and their relatives, where available. MYH11 and MYLK were screened by next‐generation sequencing. Key results: We identified heterozygous missense variants in ACTG2 in 7 of 17 families ( 41%) diagnosed with CIPO and its associated conditions. We also identified a previously unpublished missense mutation (c.443C>T, p.Arg148Leu) in one family. One case presented with megacystis‐microcolon‐intestinal hypoperistalsis syndrome in utero with subsequent termination of pregnancy at 28 weeks' gestation. All of the substitutions identified occurred at arginine residues. No likely pathogenic variants in LMOD1, MYH11, or MYLK were identified within our cohort. Conclusions and inferences: ACTG2 mutations represent a significant underlying cause of primary CIPO with visceral myopathy and associated phenotypes in Australasian patients. Thus, ACTG2 sequencing should be considered in cases presenting with hypoperistalsis phenotypes with suspected visceral myopathy. It is likely that variants in other genes encoding enteric smooth muscle contractile proteins will contribute further to the genetic heterogeneity of hypoperistalsis phenotypes. Abstract : Primary CIPO is a rare, potentially life‐threatening disorder characterized by severely impaired gastrointestinal motility. We identified heterozygous missense variants in ACTG2 in 7 of 17 families ( 41%) diagnosed with CIPO and its associated conditions. We also identified a previously unpublished missense mutation (c.443C>T, p.Arg148Leu) in one family. ACTG2 mutations account for a substantial number of both pediatric and adult cases of CIPO and thus should be screened in all patients presenting with this phenotype.